Differences in game statistics between winning and losing for male wheelchair tennis players in Paralympics Games - Alejandro Sánchez-Pay; Gema Torres-Luque; Ángel Iván Fernandéz-Garcia; Davi Sanz-Rivas; José Manuel Palao Andrés (Universidade Estadual Paulista (UNESP), 2017)
ABSTRACT Aims The aim of the present study was to analyze the differences in wheelchair tennis game statistics between winning and losing sets. Methods Data were collected from the 139 sets of 64 matches played by 64 males' players in the 2012 Paralympics Games. The variables studied were grouped in four groups: variables related to serve, to return, to winners and errors, and to net point. Data was collected from official website of the Paralympics Games. A univariate (Wilcoxon test) and multivariate (discriminant) analysis of data was done to the study the four groups of variable in relation to the result of the set (win or lose). Results The result showed that winning players commit fewer errors and achieved more winning shots than losing players. Conclusion The values presented could be used as a reference for practice and competition in wheelchair tennis players.